EXTENT OF COVERAGE OF MINERAL SURFACES BY ORGANIC MATTER IN MARINE SEDIMENTS - ISOMERICALLY PURE ANIONIC SURFACTANTS - Mayer L.M. (My University, 1999)
Organic matter loading in continental margin sediments frequently occurs at a concentration equivalent to a monolayer coating of mineral grains, raising the question of whether adsorbed organic matter is indeed dispersed over all mineral surfaces. A method was developed to address this configurational issue using the energetics of gas adsorption on oxide surfaces. Enthalpies of gas adsorption were assessed using the C constant of the Brunauer-Emmett-Teller (BET) equation. Physisorption of nitrogen or argon gas involves higher enthalpies onto naked than onto organically coated oxide surfaces. Studies on model adsorbate-adsorbent systems provided an algorithm relating gas adsorption energetics to the fraction of surface coated with organic matter. Application of this algorithm to marine aluminosilicate sediments shows that those with low to moderate loadings of organic matter (<3 mg organic carbon m-2) have generally less than 15% of their surfaces coated. Most minerals in these sediments, which account for most sediments in the ocean, therefore present a largely naked aluminosilicate surface to aqueous solutions.